Penerapan Model The Power Of Two Dalam Meningkatkan kemampuan Menulis text Peserta Didik Kelas IX 4 Materi Ungkapan Harapan atau Do’a dan ucapan selamat Pada MTsN 3 Padang Pariaman TP 2022/2023 - Emilizar (JURNAL ILMIAH RESEARCH STUDENT, 2023)
The background of the research is that it shows the low learning outcomes of students, which can be seen from the average score of students' daily test results on the material Expressions of hope and prayer and greetings, namely 65. The average score is still below the KKM set by madrasas, namely 70. This shows student learning outcomes are still low. The research method is Classroom Action Research (PTK). The research was carried out in two cycles, each cycle consisting of planning, implementing actions, observing and reflecting. The research subjects were students of class IX 4 MTsN 3 Padang Pariaman, totaling 34 students. Data collection is qualitative and quantitative data. Qualitative data in the form of observation sheets on the implementation of the Power Of Two learning model and student motivation questionnaire sheets. Meanwhile, quantitative data consists of data obtained from 1) the percentage of implementation of the learning model obtained from the number of Yes and No answers on the observation sheet, 2) the percentage of student learning motivation and 3) the increase in learning outcomes obtained by using the Power Of Two learning model. The results obtained from this research include: 1) the implementation of the Power Of Two learning model is categorized as very good, 2) the learning outcomes for each cycle have increased above the KKM value of 70. Student learning outcomes in cycle I are 82.00. Student learning outcomes in cycle II it was 91.00. This shows an increase from cycles I and II in student learning motivation through the application of the Power of Two learning model with an average score of 86.5% in the very high category. Application of the Power of Two learning model. can increase students' activeness in learning, and can help students stay focused and alert in various learning situations that are occurring so that there is an increase in the completeness of learning outcomes.